a) 6x + 4 = 8 + 4x b) 5 – 2(x + 2) = 9 c) 2(x + 2) – 3(x – 1) + 8 = 3x – 1



Odpowiedź :

Hej!

6x + 4 = 8 + 4x

6x - 4x = 8 - 4

2x = 4 / : 2

x = 2

5 - 2(x + 2) = 9

5 - 2x - 4 = 9

-2x = 9 - 5 + 4

-2x = 8 / : (-2)

x = -4

2(x + 2) - 3(x - 1) + 8 = 3x - 1

2x + 4 - 3x + 3 + 8 = 3x - 1

2x - 3x - 3x = -1 - 4 - 3 - 8

-4x = -16 / : (-4)

x = 4

Pozdrawiam! - Julka

Odpowiedź:

A) 6x-4x=8-4

2x=4/2

X=2

B) 5 - 2x -4 =9

-2x=9-5+4

-2x=8

X= -4

C) 2x+4-3x+3+8=3x-1

2x-3x-3x=-4-8-3-1

-4x=-16

X=4

Szczegółowe wyjaśnienie: